Determination of Cross-Border Post Points Based on Geospatial Intelligence for Territorial Defense of the Unitary State of the Republic of Indonesia: Literature Review - Rifai, Bachtiar; Poniman, Aris; Gultom, Rudy Agus Gumilang (Formosa Journal of Science and Technology, 2024)
The location of cross-border posts is crucial for Indonesia's land and maritime security and combating illegal activity. Geographical intelligence technology like sensors and machine learning can help find crucial sites. GEOINT and international cooperation enable monitoring, threat detection, and trade regulation. This study uses a literature review to examine how GEOINT helps Indonesia defend its territory. This research collects, analyzes, and synthesizes important scientific studies using a literature review. Our literature search used relevant terms in scientific databases. The selected literature covers GIS, GEOINT, Satellites, Drones, and cross-border posts. Analysis identified major conclusions and research gaps. Geospatial intelligence technology (GEOINT), which uses drones and satellites to monitor and provide high-resolution data, is effective at detecting and responding to threats in Indonesia's extensive border areas. Additionally, this technology helps find the right cross-border post. Geographic information systems (GIS) must assist centralized data management and defense agency collaboration to strengthen border security. GEOINT supports strategic cross-border post placement decisions to secure Indonesia's borders. For regional defense, national security, and stability in the face of complex global problems, the latest and most effective technologies must be developed and used.